Awareness and Use of HIV Self-Testing Among Men Who Have Sex With Men Remains Low in Spain 2 Years After Its Authorization - Guerras, Juan-Miguel; Hoyos, Juan; de la Fuente, Luis; Donat, Marta; Pulido, José; Sordo, Luis; García de Olalla, Patricia; Belza, María-José (Frontiers in Public Health, 2022)
Objectives: HIV self-testing has been available in Spain since 2017 as a diagnostic tool to promote earlier diagnosis. We aimed to assess awareness and previous use of HIV self-testing in a sample of men who have sex with men (MSM) recruited online more than two years after its legal authorization in Spain. Methods: We analyzed 5492 MSM recruited between May and July 2020 in gay dating apps/websites and other social networks. We estimated the proportion of participants who were aware of the existence of HIV self-testing and the proportion who reported previous use. To identify factors associated with both outcomes we built two Poisson regression models. Among those who reported previous use we described several aspects related to their last self-test. Results: Awareness of HIV self-test was reported by 29.7% and its previous use by 5% of participants. Awareness was independently associated with recruitment in gay dating apps/websites, being >= 40 years old, born in Spain-other European countries, having higher educational level, living in medium-small municipalities and living sex life openly. Independent associations were also found with having received a sexually transmitted infection diagnosis (STI) or an HIV negative test in the last 12 months, and being HIV positive. Use was significantly higher among participants who were paid for sex or diagnosed with an STI in the last 12 months and who received their last HIV test in the preceding year. Self-testing occurred recently, with kits acquired at pharmacies and carried out alone. Conclusion: Awareness and use probably have not increased sufficiently in order to make a relevant impact to the promotion of early HIV diagnosis. Additional efforts, mainly focused on less favored MSM, should be made to take better advantage of the possibilities offered by this testing option.